Visualizing Sequences in the Social Sciences: Relative Frequency Sequence Plots - Anette Eva Fasang; Tim Futing Liao (Sociological Methods & Research, 2014)
Visualization is a potentially powerful tool for exploration and complexity reduction of categorical sequence data. This article discusses currently available sequence visualization against established criteria for graphical excellence in the visual display of quantitative information. Existing sequence graphs fall into two groups: They either represent categorical sequences or summarize them. The authors propose relative frequency sequence plots as an informative way of graphing sequence data and as a bridge between data representation graphs and data summarization graphs. The efficacy of the proposed plot is assessed by the R2 and the F statistics. The applicability of the proposed graphs is demonstrated using data from the German Life History Study on women's family formation.
Keywords: 330; sequence analysis; visualization; optimal matching; sequence index plots